From Nations to the European Union: A New Emerging Type of Society (Global Journal of Human-Social Science, 2024)
Revisiting the sociological concepts of nation and reciprocities formulated by Marcel Mauss the hypothesis of the European Union is put forward as a new type of society in which each member is integrated by the multiple differences in and between themselves unlike nations whose homogenizing tendency comes from direct reciprocity between each member and the entire society In this sense supranational unions would result in communities that are both originally and intentionally diverse while such international relations of indirect reciprocities within their scope would make national citizenships permeable to human diversity mainly cultural in general Therefore the current unification of European nations is a case whose study can foresee problems and possibilities of such unions to be undertaken in other planetary quadrants
Keywords: European union; nation; diversity; marcel mauss